Landfill site selection using geographical information system and multi criteria decision analysis in Johor Bharu, Malaysia - Zaudi, Muhammad Amar (2015)
Rapid economic growth and urban transformation played a major role to solid waste management problems in Malaysia. Solid waste management is one of the most challenging environmental problems. Despite the enormous amount effort and management strategies the government is applying in recent years, yet the waste management standards in Malaysia did not yield significant impact. Johor Bahru is one of most developing city and also highest of populations in Malaysia. This fact led to increase in waste generation. Instead of using 3Rs which represent reuse, reduce and recycle to diminish waste, the landfill has been identified as the most cost-effective system of solid waste disposal for most urban areas in developing countries. The objectives of this study is to determine the suitable parameters for landfill siting, to delineate and characterized the suitability of various areas and also to optimized the landfill site selection technique using GIS and MCDA methods. Data used in this research were collected from various government agencies. Data such as map were converted into digital map and undergo GIS overlaying process to identify the suitable new landfill sites. Several guidelines from government agencies and local authorities were used to guide in selecting suitable site for new landfill. The final overlay process produces four possible areas for new landfill in Johor Bahru. Furthermore, to enhance these possible sites, MCDA techniques which are Analytical Hierarchy Process and Simple Additive Weighting were used. The method sets the factors clearly and helps experts and NGOs to participate so that the lack of information or any opposition can be discussed, scored and weighted separately. AHP is a tool that has broad applicability in waste management and particularly makes assessments, prioritization and selection among waste management options more readily measurable. Even more,combining GIS and AHP techniques became more effective since this combining techniques mix all possibilities and between technologies and also human logic.